The Protective Effect of Dietary Phytosterols on Cancer Risk: A Systematic Meta-Analysis. (23rd June 2019) - Jiang, Lu; Zhao, Xin; Xu, Jun; Li, Chujun; Yu, Yue; Wang, Wei; Zhu, Lingjun
Abstract : Backgrounds/Aims. Many studies have explored the association between dietary phytosterols and cancer risk, but the results have been inconsistent. We aimed to provide a synopsis of the current understanding of phytosterol intake for cancer risk through a systematic evaluation of the results from previous studies. Methods. We performed a literature search of PUBMED, EMBASE, CNKI, and Wanfang, and studies published before May 2019 focusing on dietary total phytosterols, β -sitosterol, campesterol, stigmasterol, β -sitostanol, and campestanol, as well as their relationships with cancer risk, were included in this meta-analysis. Summaries of the relative risks from 11 case-control and case-cohort studies were eventually estimated by randomized or fixed effects models. Results. The summary relative risk for the highest versus the lowest intake was 0.63 (95% confidence interval [CI] = 0.49–0.81) for total phytosterols, 0.74 (95% CI = 0.54–1.02) for β -sitosterol, 0.72 (95% CI = 0.51–1.00) for campesterol, 0.83 (95% CI = 0.60–1.16) for stigmasterol, 1.12 (95% CI = 0.96–1.32) for β -sitostanol, and 0.77 (95% CI = 0.65–0.90) for campestanol. In a dose-response analysis, the results suggested a linear association for campesterol and a nonlinear association for total phytosterol intake. Conclusion. Our findings support the hypothesis that high phytosterol intake is inversely related to risk of cancer. Further studies with prospective designs that control for vital confounders and investigate the important anticancer effects of dietary phytosterols are warranted.